2020
DOI: 10.1093/conphys/coz110
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and stress-induced corticosterone levels across birds and reptiles do not reflect urbanization levels

Abstract: Rates of human-induced environmental change continue increasing with human population size, potentially altering animal physiology and negatively affecting wildlife. Researchers often use glucocorticoid concentrations (hormones that can be associated with stressors) to gauge the impact of anthropogenic factors (e.g. urbanization, noise and light pollution). Yet, no general relationships between human-induced environmental change and glucocorticoids have emerged. Given the number of recent studies reporting bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 69 publications
6
33
0
Order By: Relevance
“…For example, a meta-analysis on fishes showed that anthropogenic noise can have negative effects on their behaviour and physiology, but the fitness consequences depended on the noise source [72]. Similarly, a recent comparative analysis found that noise, but not light, pollution was negatively associated with baseline corticosterone levels in birds [73]. The generic use of 'urban area' as a proxy for the presence of anthropogenic stress might be too crude an index if it includes cities that vary in their extent of urbanization (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a meta-analysis on fishes showed that anthropogenic noise can have negative effects on their behaviour and physiology, but the fitness consequences depended on the noise source [72]. Similarly, a recent comparative analysis found that noise, but not light, pollution was negatively associated with baseline corticosterone levels in birds [73]. The generic use of 'urban area' as a proxy for the presence of anthropogenic stress might be too crude an index if it includes cities that vary in their extent of urbanization (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…2019; Injaian et al. 2020). Hormone data and other continuous variables were natural log‐transformed.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of noise, whereas some studies revealed that traffic noise could elicit an increment or descend in baseline CORT levels (Crino et al 2011;Kleist et al 2018, respectively), others detected no change in CORT levels in experimental (Injaian et al 2019;Angelier et al 2016) and correlational (Casasole et al 2017) set ups. The fact that rural-airport nestlings exhibited an overall good body condition and oxidative status may indicate that they do not perceive aircraft noise as a stressor, or that tree sparrow nestlings are habituated to this stressor (Dickens and Romero 2013;Injaian et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of perturbations, the organism keeps CORT concentrations at basal levels through modulations of the hypothalamus-pituitary-adrenal (HPA) axis (Sapolsky et al 2000). Chronic exposure to stressors can disrupt the correct functioning of the HPA axis, altering basal CORT levels either by increasing or reducing them (Dickens and Romero 2013;Injaian et al 2020). Therefore, long-term exposure to situations that may alter HPA responses can result in the impairment of different aspects of animal physiology if habituation is not achieved.…”
Section: Introductionmentioning
confidence: 99%